A meta-analysis of reference markers of bone turnover for prediction of fracture - Johansson, H; Odén, A; Kanis, J; McCloskey, E; Morris, H; Cooper, C; Cooper, C; Vasikaran, S; Vasikaran, S (2014)
The aim of this report was to summarize the clinical performance of two reference bone turnover markers (BTMs) in the prediction of fracture risk. We used an updated systematic review to examine the performance characteristics of serum procollagen type I N propeptide (s-PINP) and serum C-terminal cross-linking telopeptide of type I collagen (s-CTX) in fracture risk prediction in untreated individuals in prospective cohort studies. We excluded cross-sectional studies. Ten potentially eligible publications were identified and six included in the meta-analysis. There was a significant association between s-PINP and the risk of fracture. The hazard ratio per SD increase in s-PINP (gradient of risk [GR]) was 1.23 (95 % CI 1.09-1.39) for men and women combined unadjusted for bone mineral density. There was also a significant association between s-CTX and risk of fracture, GR = 1.18 (95 % CI 1.05-1.34) unadjusted for bone mineral density. For the outcome of hip fracture, the association between s-CTX and risk of fracture was slightly higher, 1.23 (95 % CI 1.04-1.47). Thus, there is a modest but significant association between BTMs and risk of future fractures. © 2014 Springer Science+Business Media New York.